Total phenolic contents, flavonoids, and antioxidant activity of the aerial parts extracts of (Calotropis procera) naturally growing in Samnu Oasis, southwest of Libya - Salem Mousbah Kalifa Alnass,; Bader Mohamed Bader Suliman, (African Journal of Advanced Pure and Applied Sciences, 2024)
The present study highlights the importance of "Calotropis. proceraa (Aiton) W. T. Aiton" [5]. as an important source of many bioactive substances. Therefore, it can be used in pharmaceutical industries. The present study seeks to quantify the overall phenolic and flavonoid content in the aerial parts extracts of (C. procera), besides evaluating its antioxidant potential. This research is significant as it will contribute to the understanding regarding the therapeutic qualities of the plant (C. procera) and focus on one of the natural resources with antioxidant capacity. Results of phytochemical screening of different aerial parts extracts of C. procera presented and reveal that the flavonoids were present in extracts of leaves, flowers, and fruits (6.55, 4.59, and 4.67 mg/g dry weight) respectively, as well as the phenolic concentrations showed were present in extracts of leaves, flowers, and fruits (10.45, 7.22, and 6.55 mg/g dry weight), respectively. Moreover, results of the anti-oxidant test showed that the highest anti-oxidant activity was present in methanolic extracts of leaves with an IC50 value of (0.17 mg/ml). While the lowest anti-oxidant activity was attained from the extract of flowers with an IC50 value of 0.24 mg/ml and presented in methanolic extracts of fruits with an IC50 value of 0.19 mg/ml. Based on in vitro tests, a relationship was observed among the outcomes from antioxidant tests and the levels of total phenolics and flavonoids. Besides, C. procera is considered promising, good candidates for natural resources of anti-oxidants for medical uses.